Evaluasi Pelaksanaan Reviu Laporan Kinerja Instansi Pemerintah (LKjIP) oleh APIP Kota Pekanbaru: Pendekatan Model Evaluasi CIPP - Aisyah Noviyanti; Meyzi Heriyanto; Hasim As’ari (Policy, Law and Political Research Center, 2026)
The review of Government Agency Performance Reports (LKjIP) conducted by the Government Internal Supervisory Apparatus (APIP) is a crucial instrument for ensuring the quality of public sector performance accountability. However, in practice, the implementation of LKjIP reviews is not always followed by substantive improvements in performance reporting quality. This study aims to evaluate the implementation of LKjIP reviews by APIP in Pekanbaru City using the CIPP Evaluation Model (Context, Input, Process, Product). The study adopts a qualitative evaluative approach, with data collected through in-depth interviews, document analysis, and limited observation. Informants were purposively selected from APIP officials and relevant stakeholders involved in the preparation and utilization of LKjIP. Data analysis was conducted interactively by categorizing findings according to the CIPP dimensions. The results indicate that, normatively, LKjIP reviews have been implemented in accordance with applicable regulations and have produced Review Result Reports as a form of limited assurance. Nevertheless, in terms of context, input, process, and product, the implementation of LKjIP reviews has not fully contributed to substantive improvements in performance accountability. Organizational readiness gaps, variations in APIP competencies, limitations in performance data quality, and weak follow-up mechanisms were identified as key factors constraining the effectiveness of the review process. This study concludes that a gap remains between normative compliance and the substantive impact of LKjIP reviews.